Investigation of power transfer in QAB converter via phase shift modulation - Suliana, Ab Ghani; Hamdan, Daniyal; Nur Huda, Ramlan; Tiong, Meng Chung (Universiti Malaysia Pahang, 2018)
In line with high demand of renewable energy as well as the energy storage, the multiport DC-DC converters topology have recently received a lot of attention due to its own advantages. In this paper, a bidirectional quad active bridge (QAB) DC-DC converter with high frequency transformer is presented. Full bridge power converter is employed and the phase shift modulation is used in investigating the power transfer of QAB converter. In applying this proposed modulation, the changing or amount of delivering and receiving power in the QAB converter are influenced by the phase shift. Multiple cases of QAB config-uration have been evaluated by 1) Multi-input single-output (balanced voltage source); 2) Multi-input single output (unbalanced voltage source); 3) Multi-input multi-output (balanced voltage source); and 4) Single-input multi-output (unbal-anced load). The simulation results of a 2.5 kW system is analyzed through MATLAB/Simulink. Also, the power efficiency is discussed through this simu-lation. It is found out that maximum power can be achieved at 90° phase shift.